Method for improving surface free energy of carbon black
By performing heat treatment of carbon black at 1300-2500°C under argon protection, the problem of insufficient free energy on the surface of carbon black is solved, and its surface activity and adsorption capacity are significantly improved, and the mechanical and conductive properties of rubber products are improved.
Patent Information
- Application Number
- CN202411942589.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The surface free energy of existing carbon black is insufficient, making it difficult to meet the high mechanical strength, wear resistance and conductive properties of rubber products.
The carbon black is heat treated under the protection of argon, and the temperature is controlled at 1300-2500°C to change the number and type of functional groups on the surface of the carbon black to improve its surface activity.
The surface free energy of carbon black is significantly improved through heat treatment, and its adsorption ability to rubber macromolecules is enhanced, thereby improving the mechanical and conductive properties of rubber products.
Smart Images

Figure CN119752224A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon black modification, and in particular to a method for improving the surface free energy of carbon black. Background Art
[0002] Carbon black is a granular substance composed of carbon elements, which is generally prepared by gas phase method and precipitation method. As an important carbon material, carbon black has the characteristics of high specific surface area, good adsorption performance and chemical stability, and is widely used in the rubber industry as a reinforcing filler. By adding carbon black, the mechanical strength, wear resistance, aging resistance and electrical conductivity of rubber products can be improved.
[0003] The performance of carbon black is related to its surface characteristics, and the surface activity is determined by the surface free energy. Generally speaking, the better the surface activity of carbon black, the better its reinforcing effect on rubber. The surface properties of carbon black in its original state are often difficult to meet the requirements. Therefore, how to improve the surface free energy of carbon black is of great significance to improving the rubber reinforcement effect. Summary of the invention
[0004] In view of this, an object of the present invention is to provide a method for increasing the surface free energy of carbon black.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The invention provides a method for improving the surface free energy of carbon black, comprising the following steps: heat-treating the carbon black under argon protection; the temperature of the heat treatment is 1300-2500°C.
[0007] Preferably, the carbon black includes one or more of N115 carbon black, N330 carbon black, N550 carbon black and N660 carbon black.
[0008] Preferably, the heat treatment is carried out for 2 hours.
[0009] Preferably, after the heat treatment is completed, the carbon black is taken out after the furnace cavity is naturally cooled to room temperature.
[0010] Preferably, the carbon black is placed in a graphite crucible for the heat treatment.
[0011] Preferably, the heat treatment temperature is 2500°C.
[0012] Preferably, the heat treatment temperature is 2200°C.
[0013] Preferably, the heat treatment temperature is 1900°C.
[0014] Preferably, the heat treatment temperature is 1600°C.
[0015] Preferably, the heat treatment temperature is 1300°C.
[0016] The present invention provides a method for increasing the surface free energy of carbon black, comprising the following steps: heat treating the carbon black under argon protection; the temperature of the heat treatment is 1300-2500° C. The present invention heat treats the carbon black at a specific temperature to affect the number and type of functional groups on the surface of the carbon black, thereby affecting the chemical adsorption (including polar adsorption and non-polar adsorption) on the surface of the carbon black, thereby achieving the purpose of increasing the surface activity of the carbon black.
[0017] Inverse gas chromatography (IGC) is one of the effective methods for detecting the surface free energy of carbon black. This method determines the adsorption free energy increment of carbon black to a series of solvents with different polarities, and then obtains the surface free energy of carbon black. The IGC method can measure the adsorption free energy increment of carbon black to each methylene group, which represents the adsorption capacity of carbon black to rubber macromolecules, and further obtain the surface dispersion free energy. This experiment used four non-polar probe molecules (n-pentane, n-hexane, n-heptane, n-octane) and four polar probe molecules (tetrahydrofuran, acetonitrile, acetone, chloroform) to interact with carbon black samples, and measured the surface free energy of heat-treated N330 and N550 carbon blacks. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The total surface energy of N330 carbon black after heat treatment at different temperatures;
[0019] Figure 2 The total surface energy of N550 carbon black after heat treatment at different temperatures;
[0020] Figure 3 This is the surface energy change diagram of N330 and N550 carbon black before heat treatment and after heat treatment at 1300℃. DETAILED DESCRIPTION
[0021] The invention provides a method for improving the surface free energy of carbon black, comprising the following steps: heat-treating the carbon black under argon protection; the temperature of the heat treatment is 1300-2500°C.
[0022] In the present invention, the carbon black preferably includes one or more of N115 carbon black, N330 carbon black, N550 carbon black and N660 carbon black.
[0023] In the present invention, the heat treatment time is preferably 2 hours.
[0024] In the present invention, the temperature of the heat treatment is preferably 1300°C, 1600°C, 1900°C, 2200°C or 2500°C; when the temperature of the heat treatment is 2500°C, the surface activity of carbon black is most significantly improved.
[0025] The present invention preferably places the carbon black in a graphite crucible for the heat treatment. After the carbon black is placed in the graphite crucible, the head cover does not need to be tightened, and the heat treatment can be performed by slightly tightening it.
[0026] In the heat treatment process of the present invention, the functional groups on the surface of carbon black change, thereby affecting the surface activity of the carbon black.
[0027] After the heat treatment is completed, the carbon black is preferably taken out after the furnace cavity is naturally cooled to room temperature.
[0028] The method for increasing the surface free energy of carbon black provided by the present invention is described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0029] Examples 1 to 5
[0030] Weigh 10g of N115 carbon black sample respectively, and put the carbon black into the graphite crucible as it is. After the crucible is loaded with carbon black, the head cover does not need to be tightened, just slightly tighten it and cover it. Then put the sample into a high-temperature boiler for high-temperature heat treatment, choose argon sintering, turn on the argon gas, set the temperature that the high-temperature furnace needs to reach (1300℃, 1600℃, 1900℃, 2200℃, 2500℃), and start timing. After reaching the preset temperature, keep it warm for 2 hours, then turn off the power of the high-temperature boiler, slowly cool it to room temperature and take out the sample.
[0031] Embodiments 6 to 10
[0032] The difference from Examples 1 to 4 is that N330 carbon black is used and the heat treatment temperatures are 1300°C, 1600°C, 1900°C, 2200°C and 2500°C respectively.
[0033] Examples 11 to 15
[0034] The difference from Examples 1 to 4 is that N550 carbon black is used and the heat treatment temperatures are 1300°C, 1600°C, 1900°C, 2200°C and 2500°C respectively.
[0035] Embodiments 16 to 20
[0036] The difference from Examples 1 to 4 is that N660 carbon black is used and the heat treatment temperatures are 1300°C, 1600°C, 1900°C, 2200°C and 2500°C respectively.
[0037] Characterization:
[0038] 1. Acid-base titration
[0039] The surface activity of carbon black is affected by adsorption. The content of functional groups affects the chemical adsorption (including polar adsorption and non-polar adsorption) of the carbon black surface, which in turn affects the change of its surface activity. The oxygen-containing groups on the surface of carbon black mainly include acidic oxygen-containing groups such as carboxyl, phenolic hydroxyl, and lactone. These three functional groups can be directly determined by acid-base titration. Among them, the surface carboxyl group of carbon black can only react chemically with the weak base NaHCO3, that is, an acid-base neutralization reaction occurs; the medium-strong base Na2CO3 can react with the surface lactone group in addition to the surface carboxyl group; the strong base NaOH can react with the surface carboxyl and lactone groups, and the phenolic hydroxyl group on the surface of carbon black. The dosage of the three bases NaHCO3, Na2CO3, and NaOH is recorded by titration, and the content and changes of the oxygen-containing groups carboxyl, lactone, and phenolic hydroxyl on the surface of carbon black under different high temperature conditions can be calculated by formula 1.
[0040] The content of acidic oxygen-containing groups on the surface of carbon black can be calculated according to the following formula:
[0041]
[0042] In formula 1:
[0043] n—volume of alkaline solution added, mL;
[0044] C b — is the molar concentration of the alkali solution used in the reaction, mol / L;
[0045] C c — is the molar concentration of the titration acid, mol / L;
[0046] V a — is the volume of acid consumed for titration, mL;
[0047] M a — is the mass of the carbon black sample, g;
[0048] Among them, carboxyl content = A; lactone content = PA; phenol content = TP;
[0049] Where A is the carboxyl content; P is the sum of carboxyl and lactone groups; T is the total acid content.
[0050] The changes in the content of surface groups carboxyl, lactone and phenolic hydroxyl groups of N115 carbon black and the changes in its total acid content are shown in Table 1.
[0051] Table 1 Surface oxygen group content of N115 before and after heat treatment (mmoL / g)
[0052]
[0053] It can be seen from Table 1 that with the gradual increase in temperature, the content of carboxyl and phenolic hydroxyl groups on the surface of N115 carbon black shows an obvious downward trend, and the total acid content of N115 carbon black gradually decreases.
[0054] Table 2 Surface oxygen group content of N330 before and after heat treatment (mmoL / g)
[0055]
[0056] Table 3 Surface oxygen group content of N550 before and after heat treatment (mmoL / g)
[0057]
[0058] Table 4 Surface oxygen group content of N660 before and after heat treatment (mmoL / g)
[0059]
[0060] As shown in Tables 1 to 4, the contents of carboxyl and phenolic hydroxyl groups on the surface of different types of carbon black all show a downward trend as the heat treatment temperature gradually increases. This change reveals that under high temperature conditions, the unstable oxygen-containing functional groups on the surface of carbon black undergo decomposition reactions. At the same time, as the temperature increases, the total acid content of carbon black gradually decreases, which directly indicates that the total amount of oxygen-containing functional groups on the surface of carbon black is gradually decreasing.
[0061] 2. Determination of surface free energy
[0062] Inverse gas chromatography (IGC) is one of the effective methods for detecting the surface free energy of carbon black. This method determines the adsorption free energy increment of carbon black on a series of solvents with different polarities, and then obtains the surface free energy of carbon black. This experiment uses the interaction of four non-polar probe molecules (n-pentane, n-hexane, n-heptane, n-octane) and four polar probe molecules (tetrahydrofuran, acetonitrile, acetone, chloroform) on carbon black samples, and measures the surface free energy of heat-treated N330 and N550 carbon blacks.
[0063] The main steps are as follows:
[0064] (1) Preparation and loading of packed columns
[0065] This experiment uses a stainless steel filling column with a length of 50 cm, an inner diameter of 3 mm, and an outer diameter of 4 mm. The filling column needs to be cleaned before loading the sample. First, it is cleaned with acetone and then dried at high temperature. Before the experiment, 0.10 g of the carbon black to be tested is loaded into the filling column.
[0066] (2) Leak detection before using the gas chromatograph
[0067] This experiment uses three kinds of gases: air, nitrogen (carrier gas) and hydrogen. Nitrogen is an inert gas and is not dangerous, but hydrogen is a flammable and explosive gas and is very dangerous. Therefore, before conducting the experiment, the connections of the device must be leak-checked and high-purity nitrogen must be passed into the gas chromatograph and then into the double hydrogen flame ionization detector.
[0068] (3) Adjust flow rate
[0069] Install the packed column onto the adjusted gas chromatograph, and then set the carrier gas flow rate to 25 mL.
[0070] (4) Activation
[0071] After the filling column is cleaned and loaded with samples, it is necessary to activate the filling column before testing. This is to remove volatile substances and impurities on the surface of carbon black through high temperature, because these volatile substances and impurities affect the adsorption performance of carbon black and will affect the test results. Set the column box temperature to 200℃, the carrier gas flow rate to 25mL, only nitrogen is introduced, connect one end of the filling column to the injection port, and then start activation for about 12 hours. Finally, observe that the baseline of the chromatographic workstation is flat, and the activation process is completed.
[0072] (5) Inject probe molecules and start testing
[0073] After activation, cool down and connect the other end of the filling column to the detector connection port, open the air and hydrogen, and then set the injector and detector temperature to 220°C, and the column box temperature to 200°C. When the preset temperature is reached, start adjusting the hydrogen flow (the ratio of hydrogen flow to air flow is 1:10), and then start ignition. After successful ignition, test and inject 0.5uL of the probe molecule through the microinjector, and then inject it into the vaporization chamber, and obtain its retention time through the gas phase test software on the computer.
[0074] The surface activity free energy of carbon black (r s ) is composed of two parts: polar and non-polar.
[0075]
[0076] In formula 2:
[0077] ——Surface activity free energy of the nonpolar part of carbon black, also known as dispersion free energy, mJ / m 2 ; ——Surface active free energy of the polar part of carbon black, mJ / m 2 .
[0078] The surface activity free energy of carbon black was studied by using reversed-phase gas chromatography. Carbon black was used as the stationary phase and the injected solvent was used as the probe. Under the condition of infinite dilution of the probe, the adsorption force and agglomeration energy of the filler surface on the probe could be calculated from the net retention volume. The adsorption free energy calculation formula is shown in Equation 3:
[0079]
[0080] In formula 3:
[0081] -ΔG——adsorption free energy of carbon black, J / mol;
[0082] R——ideal gas constant, 8.314 J / (mol·K);
[0083] T——Temperature in the packed column, K;
[0084] C—constant, 299;
[0085] V N ——net retention volume of probe molecule, mL;
[0086] S——Specific surface area of carbon black, m 2 / g;
[0087] g——The mass of carbon black in the filling column, kg.
[0088] Substitute the experimentally measured probe molecule retention time into equation 4 to calculate the net retention volume:
[0089]
[0090] In formula 4:
[0091] D——Carrier gas flow rate, mL / min;
[0092] j——chromatographic column pressure correction factor;
[0093] t r ——Retention time of probe molecule, min;
[0094] t m ——Dead time of probe molecule, min;
[0095] P w ——Saturated vapor pressure of water at flowmeter temperature, Pa;
[0096] P0——Column outlet pressure, Pa;
[0097] T C ——Chromatographic column temperature, K;
[0098] T f——Flowmeter temperature, K.
[0099] The correction factor j is calculated according to formula 5:
[0100]
[0101] In formula 5: P i ——Chromatographic column inlet pressure, Pa.
[0102] Plot the -ΔG of a series of n-alkanes against the number of carbon atoms in the n-alkanes and calculate the change in adsorption free energy caused by each methylene group - (the slope obtained by linear fitting), γ can be calculated s d :
[0103] Surface free energy of non-polar part of carbon black:
[0104]
[0105] In formula 6:
[0106] N A ——Avogadro's constant, 6.022×10 23 ;
[0107] ——The area occupied by a methylene group, 0.06nm 2 ;
[0108] ——Surface energy of polyethylene, 35mJ / m 2 .
[0109] The -ΔG calculated from a series of normal alkanes was plotted against their molecular cross-sectional areas, and a linear relationship was obtained after linear fitting. Substituting the cross-sectional area of the polar probe molecule into the equation, the non-polar part of the molecular adsorption free energy was obtained. The polar part of the adsorption free energy was obtained by subtracting the non-polar part from the total adsorption free energy of the polar molecule, expressed as -ΔΔG.
[0110] The surface free energy calculation formula of carbon black polar part is shown in formula 7:
[0111]
[0112] In formula 7:
[0113] -ΔΔG——the difference between -ΔG of the same surface-active probe molecule and the nonpolar molecule, J / mol;
[0114] a P ——Surface area of carbon black occupied by probe molecules, nm 2 .
[0115] Table 5 Data of non-polar part of N330 carbon black heat treatment
[0116]
[0117]
[0118] Table 6 Polar part data of N330 carbon black heat treatment
[0119]
[0120]
[0121] According to Table 5 and Table 6, the total surface free energy change of N330 carbon black is shown in Table 7.
[0122] Table 7 Total surface free energy of N330 carbon black heat treatment
[0123] Temperature(℃) 1300 1600 1900 2200 2500 <![CDATA[Surface free energy (mJ / m 2 )]]> 94.5 120.7 137.9 141.8 148.4
[0124] The total surface free energy of N330 carbon black after heat treatment changes as follows Figure 1 shown.
[0125] Depend on Figure 1 From the changing trend, it can be seen that when carbon black is treated at high temperature, its surface energy gradually increases with the higher temperature. Large surface energy means strong surface adsorption capacity, that is, the surface activity is also enhanced.
[0126] The non-polar data of N550 carbon black after heat treatment are shown in Table 8, the polar data are shown in Table 9, and the total surface free energy is shown in Table 10.
[0127] Table 8 Non-polar part data of N550 carbon black heat treatment
[0128]
[0129]
[0130] Table 9 Polar part data of N550 carbon black heat treatment
[0131]
[0132]
[0133] Table 10 Surface free energy of N550 carbon black heat treatment
[0134] Temperature(℃) 1300 1600 1900 2200 2500 <![CDATA[Surface free energy (mJ / m 2 )]]> 12.9 14 10.5 14.4 15.7
[0135] The total surface free energy change of N550 carbon black is as follows Figure 2 shown.
[0136] Depend on Figure 2 As can be seen from Table 10, the change trend of the surface free energy of N550 carbon black gradually increases with the increase of temperature.
[0137] The carbon black samples at room temperature were compared with those after being treated at 1300℃. The results are as follows Figure 3 As shown. Figure 3 It can be seen that the surface free energy of carbon black increases significantly after being treated at 1300℃.
[0138] From the test of the surface free energy changes of N330 and N550 carbon blacks treated at different high temperatures, it can be seen that the surface free energy of N330 and N550 carbon blacks increases with the increase of heat treatment temperature. From the results of the previous acid-base titration, it can be inferred that the surface free energy changes of N115 and N660 carbon blacks are the same. This shows that the increase in surface free energy is related to the reduction of oxygen-containing functional groups.
[0139] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for increasing the surface free energy of carbon black, characterized in that: The following steps are involved: The carbon black is heat-treated under argon protection; the temperature of the heat treatment is 1300-2500°C.
2. The method according to claim 1, characterized in that The carbon black includes one or more of N115 carbon black, N330 carbon black, N550 carbon black and N660 carbon black.
3. The method according to claim 1, characterized in that The heat treatment holding time is 2 hours.
4. The method according to claim 1 or 3, characterized in that: After the heat treatment is completed, the carbon black is taken out after the furnace cavity is naturally cooled to room temperature.
5. The method according to claim 1, characterized in that: The carbon black is placed in a graphite crucible for the heat treatment.
6. The method according to claim 1, characterized in that The temperature of the heat treatment is 2500°C.
7. The method according to claim 1, characterized in that The temperature of the heat treatment is 2200°C.
8. The method according to claim 1, characterized in that The temperature of the heat treatment is 1900°C.
9. The method according to claim 1, characterized in that: The temperature of the heat treatment is 1600°C.
10. The method according to claim 1, characterized in that The temperature of the heat treatment is 1300°C.
Citation Information
Patent Citations
Manufacturing method of double fabric having excellent light blocking function, soft touch and melange effect, and double fabric woven by this method
KR102340615B1
System for providing alarm of leakage of chemical material and method for providing alarm of leakage of chemical material
KR102540986B1